Stylistyka artykułów poradnikowych o tematyce kulinarnej adresowanych do mężczyzn – na podstawie materiałów z miesięcznika „Men’s Health” - Smól, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The subject of the analyses in this article are food related articles addressed to men, published in the monthly “Men’s Health” in 2020. In order to encourage the readers to read texts related to broadly understood nutrition, the editors use the persuasive potential resulting from the combination of various functional styles. Colloquial, natural and casual style, which is typical of everyday communication, makes it easier to get closer to the readers, creates the impression of a close and friendly relationship and enters into a dialogue with them, while the scientific style promotes the credibility of the message and gives it a professional character. The way of providing metaphors, which is unusual for food related texts (war metaphor, automotive metaphor), as well as anthropomorphisms translate into the imagery character of the text and serve to familiarize the readers with a sphere of reality that is unknown to them.